Advances in the Biology, Imaging and Therapies for Glioblastoma - Chen, Clark C. (IntechOpen, 2011)
This book is intended for physicians and scientists with interest in glioblastoma biology, imaging and therapy. Select topics in DNA repair are presented here to demonstrate novel paradigms as they relate to therapeutic strategies. The book should serve as a supplementary text in courses and seminars as well as a general reference.